Early lung cancer in the elderly: sublobar resection provides equivalent long-term survival in comparison with lobectomy - Liu, Tieqin; Liu, Hongxu; Li, Yu (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : The worldwide population shift towards older ages will inevitably lead to more elderly patients being diagnosed with non-small cell lung cancer (NSCLC). It still remains controversial whether sublobar resection is effective in such cases at an early stage. To answer this question, we need to understand the clinical characteristics of these tumors. Material and methods : From 2004 to 2010, a total of 167 patients with stage I non-small cell lung cancer (NSCLC) of age ≥ 70 years underwent complete resection in our institution. The clinical data were retrospectively analyzed as regards gender, stage of disease, histology, smoking status, smoking amount, drinking status, surgical approaches and overall survival. Survival was analyzed by the Kaplan-Meier method and log-rank test. Results: The overall 5-year survival rate was 62.4%. There were 122 (73.1%) patients who underwent standard lobectomy resection and 45 (26.9%) patients underwent sublobar resection. Patients with different surgical approaches (lobectomy and sublobar resection) had nearly the same 5-year survival rate (60.9% vs. 63.4%, p = 0.558). Gender (p = 0.023), smoking status (p = 0.045) and smoking amount (p = 0.007) significantly influenced the prognosis. Conclusions : In elderly stage I NSCLC patients, sublobar resection is considered to be an appropriate treatment in comparison with lobectomy, as this procedure provides equivalent long-term survival.